The amino acid residue E96 of Ghd8 is crucial for the formation of the flowering repression complex Ghd7‐Ghd8‐OsHAP5C in rice. Issue 4 (2nd February 2023) - Li, Shuangle; Hu, Yong; An, Chen; Wen, Qingli; Fan, Xiaowei; Zhang, Zhanyi; Sherif, Ahmed; Liu, Haiyang; Xing, Yongzhong
Abstract: Ghd7 is an important gene involved in the photoperiod flowering pathway in rice. A Ghd7 ‐involved transcriptional regulatory network has been established, but its translational regulatory pathway is poorly understood. The mutant suppressor of overexpression of Ghd7 ( sog7 ) was identified from EMS‐induced mutagenesis on the background of ZH11 overexpressing Ghd7 . MutMap analysis revealed that SOG7 is allelic to Ghd8 and delayed flowering under long‐day (LD) conditions. Biochemical assays showed that Ghd8 interacts with OsHAP5C and Ghd7 both in vivo and in vitro . Surprisingly, a point mutation E96K in the α2 helix of the Ghd8 histone fold domain (HFD) destroyed its ability to interact with Ghd7. The prediction of the structure shows that mutated amino acid is located in the interaction region of CCT/NF‐YB/YC complexes, which alter the structure of α4 of Ghd8. This structural difference prevents the formation of complex NF‐YB/YC. The triple complex of Ghd8‐OsHAP5C‐Ghd7 directly bound to the promotor of Hd3a and downregulated the expression of Ehd1, Hd3a and RFT1, and finally resulted in a delayed heading. These findings are helpful in deeply understanding the Ghd7 ‐involved photoperiod flowering pathway and promote the elucidation of rice heading. Abstract : Forward genetics identified suppressor of overexpression of Ghd7, a new allele of Grain and heading date 8 ( Ghd8 ); the mutant protein contains the E96K alteration and promotes the expression of Heading date 3a by disrupting the formation of a complex including Ghd7, Ghd8, and the Nuclear Factor Y protein OsHAP5C.